Tolerance for Emotional Internet Infidelity and Its Correlate with Relationship Flourishing - Bernadette Nathania Octaviana; Juneman Abraham (Institute of Advanced Engineering and Science, 2018)
Until today, there is still controversy whether emotional Internet infidelity or cheating is something that can be tolerated. Existing views are diverse, influenced by geographical factors, cultural and ideological backgrounds, as well as biological theory. This present study initially suggested that the higher the relationship flourishing, the higher the tolerance for the infidelity. In an era where monogamous relationships are dynamized by the multiplication of relationship modes through online social networks, this study becomes increasingly urgent, i.e. to recommend a variable capable of providing a buffering effect to the deleterious effect of the infidelity. The study used correlational design. As much as 210 participants (55 males, 155 females, Mage=37.89 years old, SDage=10.870 years) were recruited in the Greater Area of Jakarta, Indonesia to fill out the Relationship Flourishing Scale and Internet Infidelity Tolerance-Emotional Infidelity Subscale. This study found that relationship flourishing and emotional Internet infidelity are negatively correlated (Spearman’s Rho=-0.172, p<0.05) and there is a moderating role of sex (coeff.=0.3481, p<0.05). That is, those with higher relationship flourishing would have a higher intolerance, especially among men. Such intolerance could lead to marital dissatisfaction and, at worst, divorce. The results of this study have implications for (1) an evaluation of psychometric dimensions of the Relationship Flourishing Scale, (2) the need of proposing moderating variables to be integrated into the correlational model between relationship flourishing and the infidelity, as well as (3) online applications development in detecting and managing the Internet infidelity.